A Review of Collagen Cross-Linking in Cornea and Sclera - Xiao Zhang; Xiang-chen Tao; Jian Zhang; Zhi-wei Li; Yan-yun Xu; Yu-meng Wang; Chun-xiao Zhang; Guo-ying Mu (Journal of Ophthalmology)
Riboflavin/UVA cross-linking is a technique introduced in the past decades for the treatment of keratoconus, keratectasia, and infectious keratitis. Its efficacy and safety have been investigated with clinical and laboratory studies since its first clinical application by Wollensak for the treatment of keratoconus. Although its complications are encountered during clinical practice, such as infection inducing risk, minimal invasion merits a further investigation on its future application in clinical practice. Recently, collagen cross-linking in sclera shows a promising prospect. In present study, we summarized the representative studies describing the clinical and laboratory application of collagen cross-linking published in past decades and provided our opinion on the positive and negative results of cross-linking in the treatment of ophthalmic disorders.